2022
DOI: 10.1002/ijc.34051
|View full text |Cite
|
Sign up to set email alerts
|

The landscape of genetic aberrations in myxofibrosarcoma

Abstract: Myxofibrosarcoma (MFS) is a rare subtype of sarcoma, whose genetic basis is poorly understood. We analyzed 69 MFS cases using whole-genome (WGS), whole-exome (WES) and/or targeted-sequencing (TS). Newly sequenced genomic data were combined with additional deposited 116 MFS samples. WGS identified a high number of structural variations (SVs) per tumor most frequently affecting the TP53 and RB1 loci, 40% of tumors showed a BRCAness-associated mutation signature, and evidence of chromothripsis was found in all ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 58 publications
2
17
0
Order By: Relevance
“…6,[15][16][17] MFS is a sarcoma with distinct histopathologic features 18 but only nonspecific genomic findings identified previously, including typically low TMB with alterations in TP53 and genes encoding proteins in the cell cycle. 1,2 Prior methylation array studies have shown that MFS and most UPS cluster together, supporting that they represent a histopathologic spectrum of a single disease. 4 MFS shows the highest AXL mRNA expression level in the TCGA data set compared with normal tissues, other cancer types, and even other sarcoma types.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…6,[15][16][17] MFS is a sarcoma with distinct histopathologic features 18 but only nonspecific genomic findings identified previously, including typically low TMB with alterations in TP53 and genes encoding proteins in the cell cycle. 1,2 Prior methylation array studies have shown that MFS and most UPS cluster together, supporting that they represent a histopathologic spectrum of a single disease. 4 MFS shows the highest AXL mRNA expression level in the TCGA data set compared with normal tissues, other cancer types, and even other sarcoma types.…”
Section: Discussionmentioning
confidence: 98%
“…The tumor shares overlapping genomic features with undifferentiated pleomorphic sarcoma (UPS), including widespread copy number alterations and often low tumor mutational burden (TMB, mutations/Mb) with mutations in TP53 and in genes associated with cell cycle checkpoints (RB1, CDKN2A). [1][2][3] Moreover, methylation array studies have shown that MFS and most cases of UPS cluster similarly, implying that they constitute a morphologic spectrum of a single disease. 4 Although MFS has distinct histopathologic features, no recurrent genetic alterations specific to MFS/UPS have been identified and, as a consequence, there are no effective targeted therapies.…”
mentioning
confidence: 99%
“…Available target therapies are hormone therapies, signal transduction inhibitors, gene expression modulators, apoptosis inducers, angiogenesis inhibitors, immunotherapies, and monoclonal antibodies that provide toxic molecules [ 161 ]. Sometimes, the tumors can express a multitude of genetic aberrations [ 162 ]. Mutations or variants of a single gene may have different consequences, and the response to target therapies may differ depending on the context [ 158 ].…”
Section: Therapeutic Perspectives On Biosensors and Biomarkers In Can...mentioning
confidence: 99%
“…It was found to have prognostic and predictive value for hepatocellular carcinoma together with fourteen others transcription factors (67). Recently, recurrent ZNF780A mutations were reported in myxofibrosarcomas (68). The exact cellular function of ZNF780A and its role in the development and progression of neoplasms are currently unknown.…”
Section: Figure 3 Acgh Showing the Deleted Part Of The P Arm Of Chrom...mentioning
confidence: 99%